فاعلية القطاع الخاص والمجتمع المدني لترقية جودة الخدمات الصحية - ارحاب, شادية; بريش, محمد عبد المنعم (revue mofakir, 2018)
لقد أصبح من الضروري اليوم على الدول النامية، إعادة النظر في السياسات المنتهجة لتأطير المجتمع المدني والقطاع الخاص والتخلي على سياسة شراء السلم الاجتماعي . وإن تحقيق أهداف التنمية الصحية، يتطلب وضوح هذه الأهداف وتبنيها بشكل جدي من قبل كافة الأطراف كما يتطلب توفر المرونة والشفافية والمشاركة، بالإضافة إلى توفر الموارد اللازمة لتغطية نفقات التنمية الصحية المستدامة ولا يتأتى ذلك إلا عن طريق تفعيل دور الجمعيات الأهلية الأقرب إلى الناس ومشاكلهم كإحدى أهم الفواعل في تحقيق حكامة صحية، مما يعني ضرورة تنظيم العمل الأهلي، والإبداع بإصدار قانون جديد يدعم مشاركة الجمعيات و القطاع الخاص ويساعدهما في تنمية مواردها بدورها كشريك في التنمية.   Abstract: IT has become necessary, for the develloping countries to reconsider the adopted politics to form the civil society and private sector to get rid of the Policy of affording the social peace. The achievement of health development goals requires clarity of these goals and adoping seriously by all parts. It also requires the availability of flexibility, transparency and participation. In addition, to the necessary resources to cover the costs of the sustainable health development which do not come only through activating the role of civil society organizations closest to the people and their problems , which means the need to organize civil work, and creativity through the issuance of new law that supports the participation of associations and the private sector in addition help them to develop their resources in turn as a partner in development.